(untitled) (Global Journal of Management and Business Research, 2011)
The purpose of this paper is to recognition of factors effecting to level of entrepreneurship in Islamic banking sector of Iran in order to investigating the attitude and points of view in both private and own -state banking. The paper build on existing gap articulating the team entrepreneurship, work scope, reward system, available time, successful technology, work process, staff assessment. The description survey method employed and the research approach was field work study. There is considerable gap between two types of Iranian Islamic Banking about studying the seven main variables in relation with entrepreneurship. For the Iranian Islamic banking, the analysis has implications for understanding the factors effecting on both banking sectors in Iran. The study helps by a foundation for research on how to fulfill the gap between two types of Islamic banking sectors of the entrepreneurship is one of the key elements to develop economies.